Deconstructing Mason's (un)safe (un)certainty. Issue 2 (1st May 2021) - Mc Kenny, Richard
Barry Manson's safe uncertainty framework has had a significant influence on the fields of systemic psychotherapy and systemic social work. His original 1993 paper has been cited more than 300 times, and a range of interpretations offered and applications proffered. I offer a deconstructive reading of Mason's 1993 paper, in order to better understand this phenomenon. I focus on issues of style, rhetoric, expositional emphasis, and word choice – why does Mason choose 'safe' rather than 'secure'? Using analysis by Boholm and colleagues, I set out the semantic pros and cons of using 'safe' and 'secure, ' arguing that, on balance, 'secure' is the more appropriate word for Mason's purposes. I then explore Mason's reporting of practice, in particular the shift over time from indirect to direct reporting of speech. I argue this shift underpins efforts by Mason to clarify his use of safe uncertainty. Mason's changing use of voice strongly supports the claim that his framework should not be applied to the analysis of, or responses to safeguarding, risk and protection dilemmas, for which more appropriate frameworks are available.